2017
DOI: 10.1111/hir.12159
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge into action – supporting the implementation of evidence into practice in Scotland

Abstract: Background: The knowledge into action model for NHS Scotland provides a framework for librarians and health care staff to support getting evidence into practice. Central to this model is the development of a network of knowledge brokers to facilitate identification, use, creation and sharing of knowledge. Objective: To translate the concepts described in the model into tangible activities with the intention of supporting better use of evidence in health care and subsequently improving patient outcomes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Within this emerging typology, although most brokers work across different organisations, some work intra-organisationally (Waring et al, 2013). Brokers may have a different professional affiliation from those they hope to influence (Morris et al, 2013, Davies et al, 2017 or the same (Gerrish et al, 2011, Rowley et al, 2012, be situated externally (Traynor et al, 2014) or embedded within (Chew et al, 2013). Importantly, two independent reviews concluded that broker positioning and affiliation is important to success (Bornbaum et al, 2015, Elueze, 2015.…”
Section: Knowledge Brokering -Some Theoretical Perspectives Knowledgementioning
confidence: 99%
“…Within this emerging typology, although most brokers work across different organisations, some work intra-organisationally (Waring et al, 2013). Brokers may have a different professional affiliation from those they hope to influence (Morris et al, 2013, Davies et al, 2017 or the same (Gerrish et al, 2011, Rowley et al, 2012, be situated externally (Traynor et al, 2014) or embedded within (Chew et al, 2013). Importantly, two independent reviews concluded that broker positioning and affiliation is important to success (Bornbaum et al, 2015, Elueze, 2015.…”
Section: Knowledge Brokering -Some Theoretical Perspectives Knowledgementioning
confidence: 99%
“…They can play a pivotal role as knowledge brokers in health care organisations in mobilising knowledge and evidence effectively and supporting the health care workforces to provide high quality care. Library and knowledge staff can support health care practitioners to find and evaluate information that they need through managing and sharing knowledge, and optimising required technology (Davies et al, ; Lacey Bryant et al, ; Lacey Bryant, Stewart & Goswami, ).…”
Section: Research Implicationsmentioning
confidence: 99%
“…In addition, by delivering knowledge in actionable formats, for example clinical decision support systems or decision aids, there will be more options to support KM processes. (Brice & Grant, ; Brice & Muir Gray, ; Davies et al, ; Keeling & Lambert, ; Lacey Bryant et al, ; Lacey Bryant et al, ; Plaice & Kitch, ).…”
Section: Research Implicationsmentioning
confidence: 99%
“…This article contributes to the debates about whether knowledge brokerage initiated at a national level is sustained in local contexts over time. The academic literature is now fairly well developed when it comes to identifying the issues, lessons and challenges of knowledge brokerage (see for example Ward et al 2009;2010;Partidario and Sheate, 2013;Petman et al 2016; Davies et al 2017;Powell et al 2017); but there is a dearth of literature that evaluates knowledge brokerage activities previously undertaken by national evidence-producing agencies. Such a focus also calls into question aspects of national value-producing leadership (Hartley et al, 2015;Bryson et al, 2017;Van Wart, 2017).…”
Section: Introductionmentioning
confidence: 99%